2010
DOI: 10.1203/pdr.0b013e3181c345ea
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin-II Contributes to Pulmonary Vasoconstriction in a Perinatal Model of Persistent Pulmonary Hypertension of the Newborn Secondary to Meconium Aspiration Syndrome

Abstract: Meconium aspiration syndrome (MAS) disrupts perinatal decreases in pulmonary vascular resistance (PVR) and is the commonest cause of neonatal pulmonary hypertension. The contribution of the potent vasoactive agent urotensin-II (U-II), in the pathophysiology of this condition, is unknown. In a new perinatal model of MAS, we combined measurement of circulating U-II levels with U-II receptor blockade studies. Nineteen anesthetized lambs were instrumented then randomly allocated to the following groups: 1) control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Oxygen saturations were monitored in the right foreleg using Masimo pulse oximeter (Rad 7, Masimo Corporation, Irvine, CA). These initial settings are similar to other studies in lambs with MAS ( 16 ). High PIP was required for the first few minutes to achieve adequate tidal volume (8-10ml/kg) and gradually correct PaCO 2 levels in asphyxiated lambs.…”
Section: Methodssupporting
confidence: 81%
See 1 more Smart Citation
“…Oxygen saturations were monitored in the right foreleg using Masimo pulse oximeter (Rad 7, Masimo Corporation, Irvine, CA). These initial settings are similar to other studies in lambs with MAS ( 16 ). High PIP was required for the first few minutes to achieve adequate tidal volume (8-10ml/kg) and gradually correct PaCO 2 levels in asphyxiated lambs.…”
Section: Methodssupporting
confidence: 81%
“…The majority of animal studies for meconium aspiration are conducted in postnatal (1-3 d old) piglets using human meconium instilled by positive pressure into an air-filled lung( 15 ). In the current model, meconium is aspirated by negative pressure before birth into a fluid-filled lung, similar to the human condition and is associated with HRF with an oxygenation index of 21.6 ± 4.7 in the no-suction group and 16.4 ± 3.7 in the suction group at 6 hours of age, similar to other lamb models of MAS( 16 ). A prior attempt to induce PPHN and HRF using a combination of asphyxia and meconium aspiration in preterm 160d gestation baboons (term ∼ 180d) was unsuccessful( 17 ) with concomitant asphyxia reducing the severity of MAS and PPHN.…”
Section: Discussionmentioning
confidence: 70%
“…In the second work, piglets were studied for 12 h and indeed an sPLA2 increment was noticed only in the lung lobes selectively instilled with meconium [34]. Moreover, some animals had already negotiated a part of their perinatal transition, as they were more than 1 day old and this might be a main bias [37].…”
Section: Discussionmentioning
confidence: 99%
“…Palosuran is a new potent and specific antagonist of the human U-II receptor (UT receptor) [12]. There are a limited number of studies focusing on palosuran and different U-II antagonists, which point out that U-II antagonists may lead to heart failure, cirrhosis, pulmonary HT, portal HT, and diabetic nephropathy [14,[27][28][29][30][31]. Bousette et al showed that the blockade of U-II led to a significant decrease in myocardial and endocardial fibrosis, as well as a reduction in collagen deposition [27].…”
Section: Discussionmentioning
confidence: 99%